Productivity enhancement in groundnut through Front Line Demonstrations in Krishi Vigyan Kendra, Visakhapatnam - Rao, D Uma Maheswara; Chandrasekhara, P (Indian Farming, 2015)
The front line demonstration on groundnut showed that the varieties ‘TCGS 320’ and ‘TAG 24’ were superior to local varieties and were preferred by the farmers. The economic analysis of demonstration indicated the economic viability of improved varieties as well as technology. The farmers have shown keen interest to grow these varieties in large area in the ensuing seasons. The seeds of these varieties have been multiplied and distributed to the farmers for adoption in large scale.